Institute of Metals Division - High Temperature Strength of Wrought Aluminum Powder Products (Discussion page 1334) - E. Gregory; N. J. Grant (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1955)
The creep rupture properties of wrought aluminum powder products made from five grades of sintered aluminum powder were investigated at temperatures from 400° to 900°F for rupture times up to 1000 hr. The effect of stress concentrations on materials of this type was investigated by means of notched creep rupture tests. A tentative correlation was obtained between the creep rupture properties and the structure as revealed by electron micrographs. SEVERAL papers have been published recently concerning the production and properties of wrought aluminum powder products and their possible high temperature applications. Most of the published work in this field has come from abroad, notably Switzerland, and articles by Irmann and his colleagues were summarized in English recently.'.' Most of the papers published by Dr. Irmann are principally concerned with the retention of properties (by a product which is produced from extremely fine flake powder and is subsequently hot extruded) after heating to high temperature for prolonged times. The powder may be in atomized or flake form, and during hot working the applied pressure is reported to plastically deform the aluminum powder, thus breaking the oxide skin and welding the particles together. Irmann attributes the remarkable properties to the dispersion of oxide inclusions. Specifically, the product described by Irmann is one labeled SAP (Sintered Aluminum Powder) in which the initial flake powder is so fine that at least 50 pct of the flakes have one dimension of 2 microns or less. The composition of the starting aluminum shows in percent, Fe, 0.18; Si, 0.19; Zn, 0.06; Ti, 0.03; Cu, Mn, Mg, all nil; balance Al, approximately 99.5 pct. Aluminum is not the only material that has been found to have increased resistance to deformation at elevated temperatures when produced by powder metallurgy. It has been reported by Middleton, Pf eil, and Rhodes- hat platinum has a higher recrys-tallization temperature when produced by powder metallurgy and exhibits peculiar properties, many of which are similar to those of the aluminum powder products. Difficulties were encountered in explaining the reason for the strengthening in the case of platinum since the existence of the oxide is doubtful. The authors attributed the special properties to "a small amount of suitably dispersed porosity." This theory was supported by von -~eer-leder4 in the discussion to the paper, and the similarity between this method of hardening and that suggested by Rohner in his theory of age hardening was pointed out. R. de Fleury5 attempted to explain some of the properties in terms of the modulus of elasticity and elastic limit of alumina and aluminum while von Zeerleder examined the relationship between the yield strength and the reciprocal of the powder particle size. Boenisch and WiderholtQ dealt mainly with the corrosion resistance of the powder aluminum material and compared it with other aluminum alloys. The diffusion rates of other metals in SAP and pure aluminum have been compared by Seith and Lop-mann.' They showed that the alloying metals diffuse particularly quickly in SAP possibly due to the very fine grain size. The properties of the Alcoa products were given by Lyle.' The creep rupture properties of SAP and two of the Alcoa experimental powder products were compared by Gregory and Grant hnd it was shown that these products are vastly stronger at 900°F than are the best cast and wrought alloys at 600°F. Since the publication of these data, the authors have investigated two further aluminum powder products and it is the object of this paper to show how the high temperature creep rupture properties of the five materials vary with oxide content and with the structure as revealed by electron microscopy. Materials One of the five products, SAP, a sintered aluminum product, was supplied by the Societe Anonyme pourl Industrie de l,Aluminium, Neuhausen a/RHF, Switzerland, through Dr. R. Irmann, while the others, M276, M257, M293, and M255 were supplied by the Aluminum Company of America as experimental powder metallurgical products. M255- and M293 were made from coarse and fine atomized powders, respectively. The other materials were made from flake powders with significant differences in oxide content, the details of the type of powders used in the manufacture of these materials